PECULIARITIES OF SPOUSE CONFLICTS IN CROSS-ETHNIC FAMILIES - Gulnara Gaisaevna Valiullina (Sovremennye Issledovaniâ Socialʹnyh Problem, 2018)
Purpose. The article deals with the problem of conflicts between spouses belonging to different ethnic groups which is actual as the number of such families is growing today. The objective of the current research is to study the reasons of spouse conflicts and the peculiarities of spouse interaction in conflict. The authors aimed at analyzing the role structure of the family and the character of interaction of spouses in mono-ethnic and cross-ethnic families.